“Eu sou alagoano, aonde o Guerreiro mora” : uma etnografia sobre o compartilhamento de fotografias de Guerreiro do arquivo etnográfico de Théo Brandão - Souza, Iara Ferreira de (2019)
This dissertation investigates the sharing of photos of “Guerreiro”, an immaterial patrimony of Alagoas, with three “brincantes” of active Guerreiros in Maceió/AL; they are Mrs. Marlene, Mrs. Dolores and Mr. Lourenço. This initiative is part of the project "Memory and Photography in Alagoano Folklore: from Preservation to Image Sharing", coordinated by Professor Fernanda Rechenberg. The field research occurred between 2017 and 2018. The investigation includes: a) the research on the ethnographic archive of Théo Brandão trancing his “material system” b) the participant observation at the rehearsals and presentations of the “Guerreiros São Pedro Alagoano and Vencedor Alagoano”. I also interviewed Mrs. Marlene, Mrs. Dolores and Mr. Lourenço and used the photographs to "make them speak" (the photo-elicitation method). For many years, museums were the space where researchers made expositions about socially minority groups, but these representations went through revisions after the postcolonial critique. As a response to these analyzes and criticisms museums started to re-signify collections through groups historically silenced, making them participate of shared curatorship, for example. Therefore, the memories of Mrs. Marlene, Mrs. Dolores and Mr. Lourenço re-signified the photographs of the ethnographic archive of Théo Brandão.